Upaya Pencegahan Stunting Melalui Program Pelatihan Pengolahan Makanan Tambahan (PMT) Berbasis Pangan Lokal di Desa Sorinomo Kecamatan Pekat, Kabupaten Dompu - Sari Wasila Utami; Vivin Zuhratun; Candra Januarni Kartika; Muhammad Yadinul Maulidi; Aniatul Khasanah; Meli Ayana Juniati; Puji Asma Ulandari; Nurhidayah Nurhidayah; Ziyad Nabil Pratama; Inrico Invantri Soares; A. Farid Hemon (Pascasarjana Universitas Mataram, 2023)
This activity aims to prevent stunting through training in processing additional food based on local food. Stunting prevention activities have been carried out through community participation methods, program socialization, and training in processing local food-based supplements. Activities are carried out by involving the community such as PKK mothers, pregnant women, breastfeeding mothers and the general public. The resource persons for this activity were Calabai II Nanga Kara Health Center staff and Mataram University KKN students. The training material that has been delivered is the processing of local food-based food additives and socialization of the dangers and prevention of stunting for children. KKN students are also involved by delivering material about